Panglima: Sosok Pemimipin Ideal dalam Pandangan Masyarakat Dayak (Diskursus Filosofis Berdasarkan Pemikiran Machiavelli terhadap Kepemimpinan Panglima Jilah, Pemimpin Pasukan Merah Tariu Borneo Bangkule Rajakng) - Fransesco Agnes Ranubaya; Dominikus Irpan; FX. Eko Armada Riyanto; Yohanes I Wayan Marianta (Borneo Review, 2024)
The focus of this paper is a philosophical discourse on the figure of the Panglima as an ideal leader in the beliefs of the Dayak people based on Marchiavelli's thoughts in his work, "Il Principe". An ideal leader who is wise and prudent and pays attention to the people or those he leads has always been everyone's dream. But in reality, what is often experienced by a group of organizations or even a country is usually a leader who is corrupt, dishonest and even harms the citizens of his country or the group he leads. Marchiavelli, in his book Il Principe reveals that a leader is required to be wise and firm to run and maintain his government, even in a way that is even somewhat cruel. The purpose of this paper is to find the deepest meaning of the figure of "Panglima" as the ideal leader in the Dayak community. The method used is elaboration based on Marchiavelli's philosophical thoughts about a leader towards the leadership of Panglima Jilah: Leader of the Red Army Tariu Borneo Bangkule Rajakng. Panglima Jilah appears as a leader of the Dayak Ormas group who is down to earth, listens to complaints, embraces those who are far away, and he also teaches Dayak wisdom values. On another occasion, Panglima Jilah also did not hesitate to go into the field to defend the rights of the Dayak people who experienced oppression and injustice or when Kalimantan's forests and nature were destroyed. This is the figure of the "leader" referred to by Machiavelli.